2016
DOI: 10.1080/09603409.2016.1161945
|View full text |Cite
|
Sign up to set email alerts
|

Influence of shot peening on high-temperature corrosion and corrosion-fatigue of nickel based superalloy 720Li

Abstract: 1High-temperature corrosion fatigue, a combination of corrosion with a fatigue cycle, is an emerging generic issue affecting power generation and aero gas turbine engines and has the potential to limit component life. Historically, surface treatments, such as shot peening have been used to improve component life and have been optimised for fatigue response. Research into optimisation of shot peening techniques for hot corrosion and high-temperature corrosion fatigue has shown 6-8A 230H 200% coverage to provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 13 publications
0
10
0
2
Order By: Relevance
“…Whilst this work was performed utilizing prepitted specimens, so that the exact mechanisms of cracking were not investigated, it provided insight into the peening process itself and demonstrated that residual stress was not the dominant feature but the resulting deformed grains at the surface of the material that prevents cracking. This has subsequently been confirmed [7] whereby it was shown that by optimisation of this layer, it is possible to delay cracking under conditions of both corrosion and fatigue.…”
Section: Effect Of Stressmentioning
confidence: 61%
See 1 more Smart Citation
“…Whilst this work was performed utilizing prepitted specimens, so that the exact mechanisms of cracking were not investigated, it provided insight into the peening process itself and demonstrated that residual stress was not the dominant feature but the resulting deformed grains at the surface of the material that prevents cracking. This has subsequently been confirmed [7] whereby it was shown that by optimisation of this layer, it is possible to delay cracking under conditions of both corrosion and fatigue.…”
Section: Effect Of Stressmentioning
confidence: 61%
“…Evidence suggests that time independent processes are required to provide regular disturbances to the developing oxide that allows diffusion of sulphur to the base metal. Oxide film rupture mechanisms have been shown previously [7] to affect the fatigue performance of materials under corrosive conditions. In this case temperatures were insufficient to induce creep, however it was shown that the inclusion of dwell and rate of stressing, 03001-p.5 MATEC Web of Conferences greatly affected life and under certain conditions life was extended beyond that in air.…”
Section: Effect Of Waveformmentioning
confidence: 99%
“…Shot peening has been demonstrated as a fatigue life improvement process as reported by several researchers for steel [8,162,163,164,165,166], aluminum [9,11,14,167,168,169,170,171], magnesium [7,172], nickel [97,147,173,174,175], and titanium alloys [176,177,178,179,180,181,182,183,184,185,186,187,188] and as summarized or quantified in Table 1.…”
Section: Surface Modification Techniquesmentioning
confidence: 99%
“…Observa-se que a mudança mais significativa na distribuição das T R ocorre na região superficial da estrutura tratada [12]. Medições in-situ já foram empregadas com sucesso por diversos pesquisadores para investigar propriedades de materiais [13], tais como transformações de fases [14], análise de fases [15] e T R [16], através de estudos analíticos, experimentais e computacionais [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][22][23][24][25]. Uma pesquisa cuja análise foi relacionada à relaxação das T R C induzidas por SP e a redistribuição, durante ensaios em regime de flexão rotativa de alto e de baixo ciclos em aço carbono (0,45%C 16.…”
Section: Revisão Da Literaturaunclassified
“…Devido à condição de equilíbrio mecânico, essas T R C são balanceadas pela tensão residual trativa (T R T) em todo o volume do material [1]. Os efeitos benéficos do SP incluem o incremento da vida em fadiga (retardando a nucleação de trincas de fadiga) [1,2] e o aumento da resistência à corrosão [2]. Em contraponto, há o efeito deletério das T R C relaxarem em serviço, na presença de certos elementos cruciais e cotidianos, tais como: alta temperatura (T), cargas mecânicas (cíclicas ou não) / térmicas ou termomecânicas [3].…”
Section: Introductionunclassified